Kl folk arts museum - Aimi Nabiha Mohd Kamal
KL Folks Arts Museum is a proposal of a live culture centre for information, entertainment and education. The project is to become a comprehensive centre for cultural arts, including an art museum, library, live performance plaza, outdoor amphitheatre, auditoriums and Malaysian Cultural Heritage Research Institute. The building would be a place for all people, the young and the old, the poor and the rich, the locals and the tourists, to enjoy live performance, exhibitions and cultural activities inside and outside the building along the river promenade. It is design to provide unique attractions that define the distinctive character and identity of multiracial Malaysian cultural & heritage significance.